2023
DOI: 10.1136/bmjmed-2022-000245
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in cardiovascular complications and mortality in hospital patients with covid-19: registry based observational study

Abstract: ObjectiveTo assess whether the risk of cardiovascular complications of covid-19 differ between the sexes and to determine whether any sex differences in risk are reduced in individuals with pre-existing cardiovascular disease.DesignRegistry based observational study.Setting74 hospitals across 13 countries (eight European) participating in CAPACITY-COVID (Cardiac complicAtions in Patients With SARS Corona vIrus 2 regisTrY), from March 2020 to May 2021ParticipantsAll adults (aged ≥18 years), predominantly Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Sci. 2024, 14, 273 2 of 16 complications, in a large registry-based study of 11,167 adults admitted to hospitals with COVID-19 between March 2020 and May 2021 [10]. Sex differences exist regarding body composition, sex hormones, and lipid levels, where women have a higher body fat percentage [11] and higher HDL cholesterol compared to men [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2024, 14, 273 2 of 16 complications, in a large registry-based study of 11,167 adults admitted to hospitals with COVID-19 between March 2020 and May 2021 [10]. Sex differences exist regarding body composition, sex hormones, and lipid levels, where women have a higher body fat percentage [11] and higher HDL cholesterol compared to men [12].…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2). Early in the pandemic, seminal studies evaluating short-term outcomes found that patients with COVID-19 who were hospitalized had a high incidence of fatal and nonfatal cardiovascular complications [ 5 , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , 21 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] ( Table 1A , Table 1B ). The risk of VTE was particularly high in the intensive care unit, with pooled incidence rate of 27 % in a meta-analysis of early studies [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“… Daniels et al [ 29 ], 2021 Myocarditis 1597 39.6 N/A Multicenter Outpatient Prospective patient enrollment Myocarditis occurred in 2.3 % of athletes diagnosed with COVID-19 and screened using cardiac magnetic resonance imaging. Hockham et al [ 32 ], 2023 Cardiovascular complications (myocarditis, pericarditis, endocarditis, myocardial ischemia, arrhythmia, stroke, HF, PE) 11,167 40.0 68.0 ‡ Multicenter Inpatient Detailed review of EHRs Hospitalized female patients with COVID-19 were at lower risk of cardiovascular complications (13 %) compared with men (17 %). Venturelli et al [ 33 ], 2021 Cardiovascular complications (cardiac ischemia, cardiac arrhythmia) 767 32.9 63.0 † Single center Inpatient Detailed review of EHRs Hospitalized COVID-19 patients had a higher incidence of cardiac complications such as arrhythmia, ischemia, and myocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there has been increasing recognition of specific cardiovascular complications of COVID-19 including acute coronary syndromes and myocarditis, amongst others [ 5 9 ]. Importantly, the incidence of such cardiovascular complications is greater in men than in women [ 10 , 11 ]. The mechanisms underlying these cardiovascular manifestations might be secondary to the severe inflammatory response induced by COVID-19, as well as the virus itself.…”
Section: Introductionmentioning
confidence: 99%